A SPectroscopic survey of biased halos In the Reionization Era (ASPIRE): impact of galaxies on the circumgalactic medium metal enrichment at z > 6 using the JWST and VLT - Zou, Siwei; Cai, Zheng; Wang, Feige; Fan, Xiaohui; Champagne, Jaclyn B.; Hennawi, Joseph F.; Schindler, Jan-Torge; Farina, Emanuele Paolo; Yang, Jinyi; Inayoshi, Kohei; Bañados Torres, Eduardo; Bosman, Sarah; et al. (The astrophysical journal. Part 2, Letters, 2024)
We characterize the multiphase circumgalactic medium (CGM) and galaxy properties at z = 6.0-6.5 in four quasar fields from the James Webb Space Telescope A SPectroscopic survey of biased halos In the Reionization Era (ASPIRE) program. We use the Very Large Telescope/X-shooter spectra of quasar J0305-3150 to identify one new metal absorber at z = 6.2713 with multiple transitions (O i, Mg ii, Fe ii, and C ii). They are combined with the published absorbing systems in Davies et al. at the same redshift range to form a sample of nine metal absorbers at z = 6.03-6.49. We identify eight galaxies within 1000 km s−1 and 350 kpc around the absorbing gas from the ASPIRE spectroscopic data, with their redshifts secured by [O iii] (λ λ4959, 5007) doublets and Hβ emission lines. Our spectral energy distribution fitting indicates that the absorbing galaxies have stellar masses ranging from 107.2 to 108.8 M ⊙ and metallicity between 0.02 and 0.4 solar. Notably, the z = 6.2713 system in the J0305-3150 field resides in a galaxy overdensity region, which contains two (tentatively) merging galaxies within 350 kpc and seven galaxies within 1 Mpc. We measure the relative abundances of α elements to iron ([α/Fe]) and find that the CGM gas in the most overdense region exhibits a lower [α/Fe] ratio. Our modeling of the galaxy’s chemical abundance favors a top-heavy stellar initial mass function and hints that we may be witnessing the contribution of the first generation of Population III stars to the CGM at the end of the reionization epoch.